TRANSFORMASI VISUAL: ANALISIS FORMALISME DALAM COMPOSITION V DAN COMPOSITION VII KARYA WASSILY KANDINSKY - A F, Muhamad Fathur Rouf (Narada : Jurnal Desain dan Seni, 2023)
This study analyzes visual transformation through the formalist approach in two iconic works by Wassily Kandinsky, "Composition V" and "Composition VII." Through the formalist approach, this research explores how visual elements such as lines, shapes, colors, and composition are used to create a profound transformation in a work of visual art. Furthermore, visual analysis methods are applied to dissect the aesthetic changes between these two works and their implications. The results reveal Kandinsky's evolution in aesthetic emotions, depicting abstract reality and raising questions about the boundaries of visual expression. This study contributes to an understanding of Kandinsky's works and the relevance of the formalist concept in the experience of aesthetics and visual interpretation.